Musculoskeletal manifestations of inflammatory bowel disease - Putowski, Maciej; Padała, Olga; Krupa, Adrianna; Konopelko, Michał; Piasek, Ewa (Journal of Education, Health and Sport, 2019)
Musculoskeletal manifestations are one of the most frequent extraintestinal manifestations of inflammatory bowel disease (IBD). Inflammatory of joints in IBD, both peripheral and axial arthopathies, belong to the spondyloarthritis group (SpA). The prevalence of the arthritis varies in different studies concerning around 5-14% patient with UC and 10-20% in CD. According to the Assessment in the Spondyloarthitis International Sociaty, SpA are divided into axial and peripheral SpA based on the predominant symptoms. Two main patterns of peripheral arthritis of IBD were distinguished with different clinical presentation. Type 1 is characterized by acute and self-limiting symptoms such as pain, swelling or effusion affecting less than five, preferentially large joints, usually correlating with IBD flares. Management of the underlying disease is treatment of choice. Type 2 is characterized by polyarticular symmetric arthritis mainly affecting small joints of upper limbs. Symptoms of type 2 are often persistent for months or even years, independent of disease activity, requiring long-term treatment. Both types should be differentiated from commonly occurring arthralgia also associated with corticosteroid withdrawal. In addition to SpA, enthesitis, tenosynovitis and dactylitis may be diagnosed in IBD ranging from 7% to 50% of cases. Osteoporosis is also important complication observed in IBD with multifactorial pathogenesis i.e., corticosteroid and immunosuppressive treatment, extensive small-bowel disease or resection, age, low physical activity, nutritional deficiencies. The overall prevalence of osteoporosis in IBD is approximately 10-20%.